2016
DOI: 10.4103/2279-042x.192463
|View full text |Cite
|
Sign up to set email alerts
|

Comparative evaluation between two methods of induced hypotension with infusion of Remifentanil and Labetalol during sinus endoscopy

Abstract: Objective:This study aimed to compare two methods of controlled hypotension using labetalol and remifentanil in terms of capability to create controlled hypotension and to investigate the obtained complications, and satisfaction rate of surgeon and patient during functional endoscopic sinus surgery.Methods:In this prospective clinical trial, 62 patients underwent endoscopic sinus surgery in Al-Zahra and Ayatollah Kashani Hospitals of Isfahan were divided into two groups: in the first group, 20 mg bolus dose of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 13 publications
3
17
0
Order By: Relevance
“…In this study, propofol combined with remifentanil for painless gastroscopy was shown to reduce the dosage of propofol and shorten the onset and recovery time, which was consistent with the results of previous studies [13][14] . In addition, our research found the combination of 2.5 mg/ml (PR2) and 5 mg/ml (PR3) of remifentanil with propofol signi cantly reduced the onset time and recovery time, as well as the dosage of propofol, compared with the combination of 1.25 mg/ml (PR1) of remifentanil with propofol.…”
Section: Discussionsupporting
confidence: 92%
“…In this study, propofol combined with remifentanil for painless gastroscopy was shown to reduce the dosage of propofol and shorten the onset and recovery time, which was consistent with the results of previous studies [13][14] . In addition, our research found the combination of 2.5 mg/ml (PR2) and 5 mg/ml (PR3) of remifentanil with propofol signi cantly reduced the onset time and recovery time, as well as the dosage of propofol, compared with the combination of 1.25 mg/ml (PR1) of remifentanil with propofol.…”
Section: Discussionsupporting
confidence: 92%
“…Remifentanil is often used to induce hypotension during surgery. [ 18 , 19 ] The decrease in blood pressure is thought to be due to a decrease in the regional vascular tone. [ 20 ] However, remifentanil is known for better maintenance of hemodynamic stability and the cerebral blood flow compared with other currently used opioids, [ 21 ] although the decrease in blood pressure becomes more conspicuous when it is administered in combination with propofol.…”
Section: Discussionmentioning
confidence: 99%
“…An example of such was Nagat S. et al ( 13 ) that, similar to the current study, utilized labetalol and TNG to induce controlled hypotension in sinus endoscopy operations and deduced that both drugs were effective and safe, but labetalol was introduced superior as it improved the visualization of surgical field with a lower (and safer) levels of hypotension; and also a lower level of hemorrhage with labetalol in the current study was due to less tachycardia in comparison to TNG. In another study by Sajedi et al, ( 14 ) regarding a comparison of labetalol and remifentanil administration to induce controlled hypotension while performing a sinus endoscopy, the authors concluded that despite the similarity of hemodynamic variables in both studied groups, a higher measure of hemorrhage and other complications were recorded in the labetalol group. Also, surgeons were more satisfied with the operation field conditions, while using remifentanil compared to labetalol; a result nearly similar to that of the current study.…”
Section: Discussionmentioning
confidence: 96%